2004
DOI: 10.3354/meps267099
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic detection of organic enrichment in sediments at a salmon farm is confirmed by independent groundtruthing methods

Abstract: Acoustic backscatter contrast in depositional sediments under salmon farm cages in the Bay of Fundy, Canada, was correlated with localized changes in (unknown) sediment geotechnical properties, as indicated by 4 independent measures of organic enrichment. Sediment total sulfides and redox potentials, enzyme hydrolyzable amino acids, sediment profile imaging and macrofaunal samples, taken at mid-cage positions, each rejected the null hypothesis that salmon cage footprints, defined acoustically as high backscatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…2). Eh NHE potentials observed in the same area in 2002 (data from Wildish et al 2004) and those from the nomogram (Table 2) generally fall above this regression line when S is < 750 µM and below the line at higher S concentrations (Fig. 1a).…”
Section: Eh Nhe Ph and Smentioning
confidence: 88%
See 4 more Smart Citations
“…2). Eh NHE potentials observed in the same area in 2002 (data from Wildish et al 2004) and those from the nomogram (Table 2) generally fall above this regression line when S is < 750 µM and below the line at higher S concentrations (Fig. 1a).…”
Section: Eh Nhe Ph and Smentioning
confidence: 88%
“…The transition from oxic to hypoxic sediments also matches the inflection point observed in BQI and other indices reflecting decreased biodiversity under increasingly hypoxic and anoxic conditions. Wildish et al (2004) observed high values of S (2500 to 30 000 µM) in sediment under a salmon farm in southwestern Bay of Fundy associated with a median BHQ value of 0 where Beggiatoa bacterial mats were extensive. Bacterial mats were absent at non-farm locations, S was lower (350 to 2500 µM) and median BHQ values were 8 to 9 (range: 6 to 10).…”
Section: Enrichment Effects On Benthic Quality and Biodiversity Indicesmentioning
confidence: 99%
See 3 more Smart Citations